Impactos da exclusão do ensino de português como L2 para surdos na educação básica na Paraíba - Mencato, Rosângela de Sousa (2022)
The National Curricular Common Base (BNCC) is a normative document that guides states and cities in the elaboration of their school curriculum. On 04/05/2018, the MEC Ordinance No. 331 established the Support Program for the Implementation of the National Common Curriculum Base (ProBNCC), which establishes guidelines, parameters and criteria for implementation. Thus, there is a need for states to prepare their proposals. In the state of Paraíba, the Secretary of State and Education (SEE) and the National Union of Municipal Education Directors (Undime) formulate the Curriculum Proposal. Therefore, these official documents should not “exclude” a curriculum for teaching Portuguese as L2 for the deaf, if they were prepared based on the National Education Plan (PNE), regulated by Law No. 13,005, of June 25, 2014, valid for 10 years and with 20 goals for improving the quality of Basic Education. Taking these official documents as a reference, the main objective of this research is to understand, from the BNCC and the Curricular Proposal of the State of Paraíba, the effects of the exclusion of a teaching curriculum of Portuguese as L2 for the deaf in Basic Education, in two schools located in the city of Campina Grande. This exploratory research seeks, through a collection of qualitative data, to carry out a deductive analysis, having as reference the “Content analysis”, by Bardin (2016). Through interviews with Portuguese teachers, the collected data were analyzed and classified according to pre-established categories according to research listed in the State of the art, among which we can list: RIBEIRO/ SHOLL-FRANCO (2018), MENDONÇA/ CARVALHO/ DOMINGUES/ FARIA (2018); MACEDO/ NUNES/ BENEVIDES (2020); SILVA (2018); MENCATO/ ÂNGELO (2021); LIMBERGER/ BUCHWEITZ (2019); QUADROS (2019); MENCATO, et al. (2017); SANTOS/ MELO/ FRONZA (2020); SILVA/ MENCATO (2022); SOUZA (2019); BRITO, et al. (2019); MÜLLER/ KARNOPP (2015); KARNOPP/ KLEIN (2007); SILVA (2001); RIBEIRO/ SILVA Org. (2015); QUADROS (1997); MOURA (2015); LEBEDEFF Org. (2017); SILVA/ SILVA Org. (2018); LIMA (2015), among others. The achieved results with the analysis of the interviews confirm the hypothesis of this work as true: the absence of a curriculum for teaching Portuguese as L2 for the deaf in official documents does not favor the investment of public policies in the training and qualification of teachers to work in this modality of education, which, consequently, causes linguistic damage for deaf individuals.